Developing a new treatment for superficial fungal infection using antifungal Collagen‐HSAF dressing. Issue 3 (10th March 2022) - Zhong, Jing; Yan, Xiayi; Zuo, Xin; Zhao, Xuan; Yang, Jiahui; Dou, Qin; Peng, Lulu; Zhu, Yuxiang; Xiao, Yichen; Bian, Zeran; He, Dalian; Xu, Qiushuang; et al.
Abstract: Fungal pathogens are common causes of superficial clinical infection. Their increasing drug resistance gradually makes existing antifungal drugs ineffective. Heat stable antifungal factor (HSAF) is a novel antifungal natural product with a unique structure. However, the application of HSAF has been hampered by very low yield in the current microbial producers and from extremely poor solubility in water and common solvents. In this study, we developed an effective mode of treatment applying HSAF to superficial fungal infections. The marine‐derived Lysobacter enzymogenes YC36 contains the HSAF biosynthetic gene cluster, which we activated by the interspecific signaling molecule indole. An efficient extraction strategy was used to significantly improve the purity to 95.3%. Scanning electron microscopy images revealed that the Type I collagen‐based HSAF (Col‐HSAF) has a transparent appearance and good physical properties, and the in vitro sustained‐release effect of HSAF was maintained for more than 2 weeks. The effective therapeutic concentration of Col‐HSAF against superficial fungal infection was explored, and Col‐HSAF showed good biocompatibility, lower clinical scores, mild histological changes, and antifungal capabilities in animals with Aspergillus fumigatus keratitis and cutaneous candidiasis. In conclusion, Col‐HSAF is an antifungal reagent with significant clinical value in the treatment of superficial fungal infections.